Uang Dan Lembaga Keuangan - Dhaisya Dea Maretha; Refi Yoanda Rahmatul Aulia; Riki Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research discusses the dynamics of money as a medium of exchange, store of value, and unit of account, as well as how the evolution of money has an impact on economic growth and global transactions. In addition, this paper investigates the challenges and risks facing financial institutions, such as market volatility, systemic risk, regulatory changes, and the impact of technological innovation. In this context, research using literature methods also examines the importance of financial stability and public trust in financial institutions, as well as strategies for maintaining the integrity of the financial system. Analyzing trends and changes occurring in the world of finance will provide readers with comprehensive insight into the latest developments in the financial sector, the important role of money in the economy, and how financial institutions can adapt to changes in the business and regulatory environment.